PENERAPAN MODEL EGARCH PADA ESTIMASI VOLATILITAS HARGA MINYAK KELAPA SAWIT - PRIHANDINI, YOSEVA AGUNG; DHARMAWAN, KOMANG; SARI, KARTIKA (E-Jurnal Matematika; Vol 4 No 3 (2015), 2015)
Good news and bad news (commonly known as the asymmetric effect) on the price of palm oil, has been the grounds of palm oil price volatility. Estimation of volatility needs to be conducted for the purposes of advance financial analysis namely computation of the risk factors, portfolio, futures, etc. In addition, the data of palm oil price is heterscedastical. The heteroscedasticity needs to be overcome in order to generate a sound estimation of volatility. One of the forecasting models for heteroscedastical data and that capable of explaining the good news and bad news over the commodity’s price is the Exponential Autoregressive Conditional Heterocedastic (EGARCH) model.The result of this research, the best of EGARCH models was EGARCH(1,1) with t-distribution. That base of AIC and SIC value.
Keywords: assymetric effect; good news and bad news; volatility; EGARCH